2011
DOI: 10.1645/ge-2685.1
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Tolerance of Spotted Seatrout, Cynoscion nebulosus, and Red Snapper, Lutjanus campechanus, to Experimental Infections with Amyloodinium ocellatum

Abstract: Amyloodinium ocellatum is a parasitic dinoflagellate that infects warm-water marine and estuarine fishes and causes mortalities in aquaculture. Its life cycle consists of 3 stages: a feeding trophont that parasitizes the gills and skin where it interferes with gas exchange, osmoregulation, and tissue integrity; a detached reproductive tomont; and a free-swimming infective dinospore. We compared the susceptibility and tolerance of juvenile spotted seatrout, Cynoscion nebulosus, and red snapper, Lutjanus campech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, it is best to observe trophonts in their diagnostic attachment to the epithelium in the gill tissue, by ablation of the totality or part of the first two gill arches. 24,38,44,120,159 The necessity of early detection and welfare issues lead also to the development of other tools for the detection of A. ocellatum in the tank environment, mainly with the help of genetic tools. 121…”
Section: Fresh Samples Diagnosis Of Amyloodiniosismentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is best to observe trophonts in their diagnostic attachment to the epithelium in the gill tissue, by ablation of the totality or part of the first two gill arches. 24,38,44,120,159 The necessity of early detection and welfare issues lead also to the development of other tools for the detection of A. ocellatum in the tank environment, mainly with the help of genetic tools. 121…”
Section: Fresh Samples Diagnosis Of Amyloodiniosismentioning
confidence: 99%
“…The feeding stage (trophont) of A. ocellatum, commonly attached to skin, fins, eyes, and gills, can interfere with gas exchange, osmoregulation, and tissue integrity thus resulting in spasmodic gasping, uncoordinated movements, and extensive mortalities of fish. 44 Most recently, Moreira et al 165 described that A. ocellatum dinospores and trophonts produce tissue-specific toxic compounds that may have a role in the attachment and feeding process of this parasite, opening an entirely new area on the parasite-host interaction.…”
Section: Host-parasite Interactions In a Ocellatum Infestations 41 | ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The only reference of amyloodiniosis in sparids from Persian Gulf was that one reported by Tareen (1986) during a parasitology study on Acanthopagrus cuvieri. Occurrence of amyloodiniosis was recorded by Masson et al (2011) in red snapper (Lutjanus campechanus) in USA and by Ramesh Kumar et al (2015) in silver pompano (Trachinotus blochii) in India. Saraiva et al (2011) reported massive infestation of A. ocellatum in Portuguese marine fish farms causing high mortalities in seabass, seabream and turbot.…”
Section: Introductionmentioning
confidence: 98%
“…According to a cosmopolitan distribution, this pathogen is capable of living and reproducing in different ecological habitats (temperature ranges: 16 to 30°C and salinity ranges: 10 to 60) and infesting both feral and cultured fish (Paperna, 1984). A. ocellatum causing severe morbidity and mortality in various aquaculture facilities, with attaching to gill and skin of cultured fishes and usually with rapid spread within a few days (Masson, Blaylock, & Lotz, 2011).…”
Section: Introductionmentioning
confidence: 99%